Напряженно-деформированное состояние некоторых типов профильных соединений с натягом при осевых нагрузках в ПК ANSYS - Лызько, Валерия Сергеевна; Андреев, Арнольд Георгиевич (НТУ "ХПИ", 2015)
Предметом исследования в данной работе является сравнительный анализ некоторых вариантов реализации соединений с натягом, находящихся под действием осевого давления. Исследования проводятся для таких вариантов соединений с натягом: круглый вал и круглая втулка, овальный вал и круглая втулка, вал – криволинейный квадрат и круглая втулка, шестиугольный вал и круглая втулка, круглый вал и овальная втулка, овальный вал и овальная втулка. Целью работы является выявление критических значений осевого давления и характеристик НДС деталей, соединенных между собой и, на основе этих данных, определение оптимального варианта соединения. Результаты приведены в виде графиков, рисунков и таблиц.

The subject of the work is a comparative analysis of some embodiments of compounds with tightness under the action of axial pressure. Research carried out for these connections with a tightness options: round and round the shaft sleeve, round and oval shaft sleeve, the shaft is in the form of a curved square and round sleeve, hexagonal shaft and sleeve round, round and oval shaft sleeve, oval shaft and oval sleeve. The disappearance of the contact pressure is dangerous in terms of the reliability of the connection parts, so the study of the topic is relevant today. The aim is to identify the critical values of axial pressure and characteristics of stress-strain state details, interconnected and, based on these data, the determination of the optimal variant connection. The results are shown in graphs, figures and tables.
Stress-strain state of some types of profile connections with tightness in the axial loads in the PC ANSYS
Keywords: осевое давление; НДС; круглый вал; круглая втулка; pressure coupling; thrust